Evaluating Large Language Models: Frameworks and Methodologies for AI/ML System Testing - Pandhare, Harshad Vijay (International Journal of Scientific Research and Management (IJSRM), 2024)
AbstractAs Large Language Models (LLMs) such as GPT-4, Claude, and LLaMA continue to redefine the frontiers of artificial intelligence, the challenge of evaluating these models has become increasingly complex and multifaceted. Traditional machine learning evaluation techniques—centered on metrics like accuracy, perplexity, and F1-score—are no longer sufficient to capture the breadth of capabilities, limitations, and risks associated with these powerful generative systems. This research addresses the growing demand for a robust and scalable evaluation methodology that can comprehensively assess LLMs across multiple dimensions, including performance, robustness, fairness, ethical safety, efficiency, and interpretability.The study begins with a critical examination of existing evaluation frameworks, ranging from benchmark-driven approaches and human-centered testing to adversarial prompt engineering and real-world simulation environments. By identifying the gaps in these current methodologies, the paper proposes a hybrid, multi-layered evaluation framework designed to address the limitations of isolated metrics and offer a more holistic view of LLM behavior in both controlled and dynamic settings.To validate the proposed framework, three widely-used LLMs—GPT-4, Claude 2, and LLaMA 2—were subjected to a series of comparative experiments. Quantitative and qualitative results were obtained across a range of benchmark tasks, ethical risk scenarios, and performance stress tests. The findings are presented using structured tables and visual graphs that demonstrate key trade-offs between accuracy, inference time, toxicity levels, and model robustness.Ultimately, this paper provides a reproducible and scalable blueprint for evaluating LLMs that not only informs model developers and researchers but also aids policymakers, ethicists, and organizations seeking to deploy these models responsibly. The framework's layered architecture offers flexibility for continuous evaluation, ensuring it can adapt to the rapidly evolving landscape of generative AI.